Impact of Riverine Fresh Water on Indian Summer Monsoon: Coupling a Runoff Routing Model to a Global Seasonal Forecast Model - Srivastava, Ankur; Rao, Suryachandra A.; Ghosh, Subimal (Frontiers in Climate, 2022)
Rivers form an essential component of the earth system, with ~36000 km3 riverine freshwater dumped into the global oceans every year. The role of rivers in controlling the sea-surface salinity and the ensuing air-sea interactions in the Bay of Bengal (BoB) is well known from observational studies; however, attempts to include rivers in coupled models used for seasonal prediction have been limited. The current study reports the benefits of river routing in coupled models over prescribing observational river discharge and the impact on the Indian Summer Monsoon (ISM) simulation. Seasonal hindcasts are carried out using a state-of-the-art global coupled ocean-atmosphere-land-sea ice model, the Climate Forecast System version 2, coupled to a runoff routing model. It is demonstrated that such a coupling leads to a better representation of the upper ocean stratification in northern BoB, causes mixed layer warming during July-August, and imparts a significant inter-annual variability to the mixed layer heat budget. The rainfall-runoff coupled feedback associated with ISM is captured better and remote teleconnections with the equatorial Pacific are enhanced. Improved seasonal mean temperature and salinity profiles in the northern BoB lead to the formation of a thicker barrier layer, which is closely tied to the freshwater from rivers. These processes result in an overall enhancement of the ISM rainfall simulation skill, which stems from the scale interactions between the sub-seasonal and seasonal variabilities of ISM. A significant community effort is required to reduce the biases in the land-surface processes to improve the streamflow simulations, along with better parameterization of mixing of river water with the ocean.